The Effect of Return on Assets, Current Ratio, Total Asset Turnover, and Debt to Equity Ratio on Stock Prices - Vigar Gystaviry Argyanezar; Santi Damayanti (eCo-Buss, 2024)
The purpose of this study is to investigate the impact that ROA, CR, TATO, and DER have on the stock prices of oil and gas companies that are listed on the IDX between the years 2015 and 2022. In 2022, the stock prices of eleven oil and gas businesses that were included on the IDX fell. Those who suffered the most were Akra and Apexindo Pratama Duta. In spite of the fact that AKRA's ROA increase from 4.83% to 9.12% in 2021–2022, the company's shares fell. Between the years 2015 and 2022, the prices of petroleum and natural gas stocks on the IDX were impacted by carbon reduction (CR), taxation (TATO), and demand-to-recovery (DTR strategies). Some researchers, including Kasmir and Sumarsan, discovered that ROA increases stock prices whereas DER decreases them. There is a comparison made between mining stock prices, ROA, ROE, NPM, and DER. The abstract of the Indonesian oil and gas stock price demonstrates how the success of a company's finances influences market prices. A non-random selection of six organizations was made for the study based on certain criteria. Balance sheets, income statements, equity statements, and cash flow statements that have been audited are evaluated using descriptive and verification statistical analysis. It would appear that the ROA T-statistic of X1 does not have any effect whatsoever on the values of stocks. When it comes to the most important T-statistic, the value 422 is lower than the confidence level of 95%. X2 represents the current ratio, X3 represents the total asset turnover, and X4 represents the debt to equity ratio. All three of these ratios are related to stock values. This is due to the fact that their T-statistics are increased in comparison to the primary T-statistic.